Teleworking modality in times of the COVID-19 pandemic in Ecuador - García-Rubio, Maite (2021)
The 21st century comes with a technological development that changes, renews and improves, according to the requirements of society and companies. This article aims to analyze the work modality, called teleworking in Ecuador, examine the legal regulations to apply it in the business sector, determine its evolution during the COVID-19 health pandemic decreed by Dr. Tedros Adhanom Ghebreyesus, Director of the World Health Organization on March 11, 2020 and verify the effects of its application. The methodology used was bibliographic-documentary through the analysis of the legal regulations, texts, articles, data and statistics published by the Ecuadorian state and other materials related to the subject. The results were obtained that this type of work contributed to save approximately 63,200 jobs, partially sustaining companies, increased workplace harassment and abuse by employers, lack of physical infrastructure, failures in connection systems and /or transfer of data, among others. It was concluded that telework, implemented on a mandatory basis in 2020, is an effective work alternative in the business sector, has sufficient legal regulations in force in the country and protected the health of the Ecuadorian inhabitants